2019
DOI: 10.1369/0022155419871033
|View full text |Cite
|
Sign up to set email alerts
|

Marker Expression of Interstitial Cells in Human Skeletal Muscle: An Immunohistochemical Study

Abstract: There is a growing recognition that myogenic stem cells are influenced by their microenvironment during regeneration. Several interstitial cell types have been described as supportive for myoblasts. In this role, both the pericyte as a possible progenitor for mesenchymal stem cells, and interstitial cells in the endomysium have been discussed. We have applied immunohistochemistry on normal and pathological human skeletal muscle using markers for pericytes, or progenitor cells and found a cell type co-expressin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 78 publications
(101 reference statements)
1
20
0
Order By: Relevance
“…9 IL-33 has been shown to be produced by fibro-adipogenic progenitor (FAP) cells, which are uniformly present in the interstitial space in the skeletal muscle and respond to muscle damage. 19 Our observation of higher IL-33 levels in the SS muscle compared with the deltoid muscle indicates an activation of FAPs, which are the source of adipocytes in muscle fatty infiltration. Muscle Foxp3 þ Tregs are characterized by high levels of expression of the IL-33 receptor, ST2, and are known to potentiate regeneration in acute and chronic injury models.…”
Section: Discussionmentioning
confidence: 60%
“…9 IL-33 has been shown to be produced by fibro-adipogenic progenitor (FAP) cells, which are uniformly present in the interstitial space in the skeletal muscle and respond to muscle damage. 19 Our observation of higher IL-33 levels in the SS muscle compared with the deltoid muscle indicates an activation of FAPs, which are the source of adipocytes in muscle fatty infiltration. Muscle Foxp3 þ Tregs are characterized by high levels of expression of the IL-33 receptor, ST2, and are known to potentiate regeneration in acute and chronic injury models.…”
Section: Discussionmentioning
confidence: 60%
“…CD10 expression is probably restricted to a subset of human MSC [ 62 ]. Interestingly, CD10 expression has been also confirmed on human muscle progenitor cells [ 64 ]. Evidence regarding CD34 expression in MSC is contradictory [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Instead, in severe and widespread muscle lesions, the endomysial CD10 + interstitial cells seem to lose CD34 expression and to increase PDGFRα positivity. 177 Furthermore, it was noted that CD10 is downregulated in the endomysium of atrophic myofibers, while being abundantly expressed around the neighboring hypertrophic myofibers, which further suggests that these CD10 + interstitial cells/TCs are endowed with great plasticity and may be implicated in skeletal muscle tissue repair/regeneration processes. 177…”
Section: A Reappraisal Of the Skeletal Muscle Sc Niche Microenvironment And Stromal Compartment After The Identification Of Tcsmentioning
confidence: 99%
“…8,11,132 Finally, a very recent immunohistochemical study employing different progenitor cell markers identified an interstitial cell population coexpressing CD10, CD34, CD271, and PDGFRα, which seems to correspond to the TCs, in the endomysium of the human skeletal muscle. 177 Indeed, TCs are well known to be identifiable as CD34 + PDGFRα + stromal cells, and immunoelectron microscopy clearly showed that the CD10 + interstitial cells possess the distinctive ultrastructural features of TCs, namely, very long and thin moniliform telopodes formed by the alternation of podomers and podoms. 1,4,17,177 Interestingly, the expression of CD10 is evocative of an intrinsic capacity of these cells to take part in myogenesis and muscle tissue regeneration.…”
Section: A Reappraisal Of the Skeletal Muscle Sc Niche Microenvironment And Stromal Compartment After The Identification Of Tcsmentioning
confidence: 99%
See 1 more Smart Citation